MRI evaluation of the lumbar spine ligamentum flavum & its contribution to degenerative spinal stenosis - Lian, Teh Hak (2018)
Introduction: Lumbar spinal stenosis (LSS) is a medical condition in which the spinal canal narrows and compresses the spinal cord and nerves at the level of the lumbar vertebra. Causes of spinal stenosis include: hypertrophy of ligamentum flavum, herniated intervertebral disc and hypertrophy of facet joint. Ligamentum Flavum (LF) is an anatomical structure, extends from the 2nd cervical vertebra through to the 1st sacral vertebra. It spans the vertebral lamina and forms the dorsal surface of the spinal canal. The objective of this study is to understand the contribution of ligament flavum in the pathoanatomy of degenerative lumbar spinal stenosis. Methodology : This is a retrospective cross sectional study involving MRI of 50 young patients without spinal stenosis and 50 older patients with spinal stenosis from Jan 2010 to Dec 2016 in Hospital University Sains Malaysia. The young non stenotic patients have no signs and symptoms of spinal stenosis. Meanwhile the older stenotic group of patients have signs and symptoms of spinal stenosis and were operated. Results & discussion : There is a significant strong linear relationship between thickness of LF with age among the young non-stenotic group (P <0.05) whereas in older spinal stenosis group, age has no significant relationship with thickness of LF . The thickness of LF in stenotic group is significantly thickened compared to non stenotic group (P<0.05). There were more cranial extension than caudal extension of LF in both groups and the thickest LF were situated at the sublaminar region. The location of thickest LF is situated at lower 1/3 from the inferior edge of lamina. There is no significant association between thickness of LF with the amount of herniated intervertebral disc but herniated disc mostly occurs in conjunction with thickened ligamentum flavum.Conclusion : Thickening of LF is an age dependent process ,however this increment of thickening was not seen in spinal stenosis group. In LSS group L3/L4 level has the thickest LF and has the most cranial extension. For complete flavectomy/ decompression, at least 12mm of lamina from the inferior edge has to be removed .